2015
DOI: 10.18632/oncotarget.3786
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenomic profiling of breast cancer brain metastases reveals potential for repurposing targeted therapeutics

Abstract: Breast cancer brain metastases remain a significant clinical problem. Chemotherapy is ineffective and a lack of treatment options result in poor patient outcomes. Targeted therapeutics have proven to be highly effective in primary breast cancer, but lack of molecular genomic characterization of metastatic brain tumors is hindering the development of new treatment regimens. Here we contribute to fill this void by reporting on gene copy number variation (CNV) in 10 breast cancer metastatic brain tumors, assayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
(24 reference statements)
0
18
0
1
Order By: Relevance
“…In recent years, comparative genomic hybridization (CGH) array chips have become a useful tool in detecting and mapping gene CNV [ 18 ]. To provide an overview of CNV in the leukocyte genome of HBV-HCC patients, we employed CGH array chips to analyze peripheral blood mononuclear cells (PBMCs) from 10 HCC patients who were HBV carriers.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, comparative genomic hybridization (CGH) array chips have become a useful tool in detecting and mapping gene CNV [ 18 ]. To provide an overview of CNV in the leukocyte genome of HBV-HCC patients, we employed CGH array chips to analyze peripheral blood mononuclear cells (PBMCs) from 10 HCC patients who were HBV carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al suggests that increased activation of HER3 and its downstream MAPK/AKT pathway molecules are implicated in colonization of brain metastasis [ 12 ]. Bolling-Fischer et al showed the amplified oncogenes including SOX2, PIK3CA, NTRK1, GNAS, CTNNB1 , and FGFR1 are related to the Stem Cell Pluripotency pathway [ 13 ]. Saunus et al identified novel candidates with possible roles in BCBM development including the significantly mutated genes DSC2, ST7, PIK3R1 , and SMC5 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the notion that stemness and embryonic pathways can play oncogenic roles, SOX2 expression was documented in several cancers, especially of endodermal, epithelial and neural origin [ 3 13 ]. In the breast, SOX2 expression has not been reported in healthy tissues but is detectable across different breast carcinoma (BC) subtypes [ 14 ] and particularly prominent also in certain BC-derived metastases [ 15 ]. Interestingly, SOX2 expression in BC is mostly confined to a minor subset of tumor cells and detectable at early stages of the disease as well as at relapse, suggesting that it is involved in BC stem cell biology and might represent a genetic driver event [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%